A practical guide for managing a self-sustaining colony of Deroceras reticulatum (Müller) (Mollusca: Pulmonata). Issue 9 (1st September 2020) - Billman-Jacobe, Helen; Watt, Anne; Heap, Denya; Haites, Ruth
ABSTRACT: Deroceras reticulatum also known as the Grey Field Slug is a serious agricultural and horticultural pest. Integrated pest management of D. reticulatum and other pest molluscs includes the use of chemical mollusicides, crop management practices and biological control. Research into the biology and control of D. reticulatum requires animals for experiments; however, collection of wild animals for these purposes is often not feasible due to variations in seasonal availability or geographic distribution. Additionally, the use of wild animals introduced a large amount of variation in experiments due to differing health status, age and prior environmental exposure of the animals. This paper describes protocols for the establishment and maintenance of a colony of D. reticulatum in the laboratory which can provide large numbers of eggs or animals of different ages for study.